2011
DOI: 10.1209/0295-5075/95/63003
|View full text |Cite
|
Sign up to set email alerts
|

Understanding large plastic deformation of SiC nanowires at room temperature

Abstract: -Tensile behaviors of SiC [111] nanowires with various possible microstructures have been investigated by molecular-dynamics simulations. The results show that the large plastic deformation in these nanowires is induced by the anti-parallel sliding of 3C grains along an ultrathin intergranular amorphous film parallel to the (111) plane and inclined at an angle of 19.47•

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 31 publications
(33 reference statements)
2
6
0
Order By: Relevance
“…Similar phenomenon is also observed in binary compound semiconductor (ZB SiC) nano-wires [12][13][14]37]. During tension, a GaAs NR deforms uniformly along its axis.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Similar phenomenon is also observed in binary compound semiconductor (ZB SiC) nano-wires [12][13][14]37]. During tension, a GaAs NR deforms uniformly along its axis.…”
Section: Discussionsupporting
confidence: 70%
“…This well explains the brittleness of GaAs at the macro-scale [19,21]. Since tensile brittleness and compressive ductility are also confirmed in ZB SiC NRs [12][13][14]37], it is expected that there is a similar size-dependent brittle-to-ductile transition.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Since relatively smooth fracture surfaces can be realized in structures with ultrathin lateral dimensions, it seems that self-healing may be an intrinsic property of one-dimensional nanomaterials [11][12][13][14][15]. However, self-healing has rarely been observed in GaAs NWs with lateral dimensions more than 12 nm.…”
Section: Introductionmentioning
confidence: 99%
“…For example, both electrostatic and London dispersion interactions in boron nitride were reported to be strongly dependent on the interlay spacing and stacking order, while SFs in SiC cause a large dispersion of strength and Young's modulus [5,6]. Particularly, recent deformation experiments by in situ transmission electron microscopy have confirmed that semiconductor GaAs nanowires and Mg alloys can be strengthened by nanoscale SFs [7,8].…”
mentioning
confidence: 99%